A framework for the measurement of the effectiveness of planning system in managing housing supply - Rameli, Alias; Johar, Foziah; Ho, Chin Siong (2007)
The oversupply of housing is related to the weakness and ineffectiveness of planning system in managing housing supply. The veracity of this argument has been proven by this empirical research conducted in the Johor Bahru conurbation area as the case of the study. This research reveals several weaknesses in the process and practice of housing planning, identified in the early stages of housing forecasting and formulation of housing planning policies along the preparation of structure plans and determination of land area and distribution of locations for future housing supply in the local plan. The weakness of the planning system is further exacerbated by the inefficiency of development control mechanisms failing to monitor, control and approve effectively the housing development applications. These findings result from the application of the conceptual framework formulated to lead this research. In such framework, the concept of effectiveness of planning system in managing housing supply is measured through the perspective of implementing planning mechanisms and housing planning processes. Applying certain measures, the effectiveness of this framework can be evaluated on general and detailed scales. This matter is thus the central point of discussion by this paper. In addition, a brief explanation shall follow to discuss the research problem, hence the issue of oversupply of housing, and a number of theoretical points motivating and guiding the research.